Histological change and heat shock protein 70 expression in different tissues of Japanese flounder Paralichthys olivaceus in response to elevated temperature - 柳意樊 马道远 肖志忠 徐世宏 王彦丰 王雨福 肖永双 宋宗诚 滕照军 刘清华 李军 (Chinese journal of oceanology and limnology, 2015)
High temperature influences the homeostasis of fish. We investigated the effects of elevated temperature on tissues of Japanese flounder （Paralichthys olivaceus） by analyzing the histology and heat shock protein 70 （hsp70） expression of fish reared in warm conditions. In this study, temperature was increased at 1±0.5℃/day starting at 24±0.5℃, and was kept at that temperature for 5 days before the next rise. After raising temperature at the rate up to 32±0.5℃, tissue samples from midgut, spleen, stomach, liver, muscle, gill, heart, trunk kidney and brain were collected for histological analysis and mRNA assay. Almost all the tissues showed changes in morphological structure and hsp70 level at 32±0.5℃. Histological assessment of the tissues indicated that the gill had the most serious damage, including highly severe epithelial lifting and edema, curved tips and hyperemia at the ending of the lamellars, desquamation and necrosis. The next most severe damage was found in liver and kidney. The hsp70 levels in all the tissues first increased and then decreased. The gut, stomach, muscle, heart, and brain had the highest expressions in 6 h, whereas the spleen, liver, gill and kidney had the highest expressions in 2 h. Therefore, tissues with the most significant lesions （especially gill and liver） responded much earlier （2 h） in hsp70 expression than other tissues, and these tissues demonstrated the most marked histological disruption and elevated mRNA levels, making them ideal candidates for further studies on the thermal physiology of this species.